ANALISIS RISIKO PEMBANGUNAN UNDERPASS DEWA RUCI - Trisna Sura Nata, I Gede; Adnyana Putera, I G. A; Diputra, Gd. Astawa (JURNAL SPEKTRAN; Vol 4 No 1 (2016): Vol. 4, No. 1, Januari 2016, 2016)
Abstract :The construction of Dewaruci Underpass was an attempt by the government to improve accessibility to support economic growth as well as to improve social welfare. The construction activities of Dewaruci Underpass can bring a wide range of risks, therefore it was conducted a research to identify the risks, assess the risks by analyzing the level of risk acceptance, risk mitigation and ownership of the dominant risk. This research was conductedbyqualitativedescriptivemethod, namely the field research, based on theliterature reviewandsupporting data. Data was collected bydistributing questionnaires tothe respondentsusingpurposive sampling method, whichsimplyselectingrespondentswho were competentandexperienced(expert) about the possiblerisksthatoccurduring theexecution ofthe construction of Dewaruci Underpass. The study was conductedin the area ofdevelopment projects of Dewaruci Underpass, JalanNgurahRaiBypass, Badung from March 2013toJune 2013. The results showedthat there were99risks identifiedand46(46.46%) of dominantriskcategory. The dominantrisks were most prevalentinthe projectrisks. There were105measuresto mitigatetheriskdominantwith 19mitigationmeasuresatan unacceptablerisk. Mostdominantrisksweretherisks ofcontractorsof41(58.57%) withsevenunacceptable risks.Thedominantrisksfor examples:disruption ofconstructiondue tothe density oftraffic, the mitigation measures were doingtraffic controlalong with the relevant agenciesandcarried out most ofthe majorworksoutsiderush hourtrafficandthe risk wasborne bythe contractor. Groundwater levelswereshallow, the mitigation measureswerepreparingdewateringwellsandthe pumpandput thework onthe drainagechannel, andthe risk wasborne bythe contractor.
Keywords: risk identification, riskmitigation, the dominantrisk, riskinsurer, Underpass of Dewaruci